Eco-integrated transit terminal - Cale, Franklin G. Jr. (Manila : National University, 2013)
The study aims to design a sustainable and Eco-friendly transportation hub that will help commuters as well as the motorists to decrease the traffic problems along the Aguinaldo Highway.
Chapter I. The research problem and settings -- Chapter II. Hypothesis -- Chapter III. Methodologies -- Chapter IV. Case study -- Chapter V. Analytical framework of design solution -- Chapter VI. Review of related literature -- Chapter VII. References.
Includes bibliographical references.
Keywords: TRANSPORTATION; TRANSIT TERMINAL